1974
DOI: 10.1002/j.1551-8833.1974.tb01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus Removal by Diatomaceous‐Earth Filtration—Part 1

Abstract: This study, involving the removal of bacterial viruses from water using diatomaceous‐earth filter aids, covers the comparative properties of uncoated and polyelectrolye‐coated products as they affect the process. The work is based on studies using bacteriophage T2 for Escherichia coli. Part 2, involving this virus and poliovirus virulent strain Mahoney Type I, will be reported in a later issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…17,18 Since this abundantly available silica-based filter medium, exhibiting an isoelectric point (IEP) around pH 2 is therefore generally negatively charged when immersed in water, the authors applied a nanostructured, high-specific surface area coating of zirconia to the internal surface area of extruded DE filter elements in an effort to impart a high adsorption capacity and generally positively charged surface to the filter. While promising microbiological results when filtering MS2 bacteriophages c were obtained, the applied coatings either failed to adsorb virus particles across the entire desired pH range (5)(6)(7)(8)(9), or were washed out by the passage of water through the filters.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…17,18 Since this abundantly available silica-based filter medium, exhibiting an isoelectric point (IEP) around pH 2 is therefore generally negatively charged when immersed in water, the authors applied a nanostructured, high-specific surface area coating of zirconia to the internal surface area of extruded DE filter elements in an effort to impart a high adsorption capacity and generally positively charged surface to the filter. While promising microbiological results when filtering MS2 bacteriophages c were obtained, the applied coatings either failed to adsorb virus particles across the entire desired pH range (5)(6)(7)(8)(9), or were washed out by the passage of water through the filters.…”
Section: Introductionmentioning
confidence: 96%
“…Various approaches have been presented in the literature which have taken up this challenge: diatomaceous earth (DE) modified with polyelectrolytes, 5-7 DE modified with salts/hydroxides of aluminum, iron, magnesium and calcium, 5,6,8 fiberglass and cellulose modified with salts of Al, Fe, Mg and Ca, 9 fiberglass and cellulose modified with alumina-coated colloidal silica, 10 sand modified with Fe-and Al-hydroxide, 11 and granular anthracite and granular activated carbon coated with nanoporous Al 2 O 3 . 12 These and other studies of electropositive filter media 13,14 generally show that the strongest contribution to the adsorption process is made by electrostatic forces, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate approach is to modify the surface properties of the filter media, e.g., by coating with an electropositive material. The first investigators of this approach (Brown et al, 1974a, Brown et al, 1974bFarrah et al, 1988;Farrah et al, 1991) found that iron aluminum hydroxide coating increased removal of viruses by diatomaceous earth from less than 30% to greater than 80%. Subsequently, Lukasik et al (1996Lukasik et al ( , 1999) tested removal of viruses by columns filled with fine sand (less than 0.3 mm) coated with iron aluminum hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the precipitate was removed from the filter as larger volumes of water were filtered. Brown et al (1,2) used aluminum hydroxide-coated diatomaceous earth to remove viruses from water. These authors reported that "poor adhesion of the alumina" limited the use of such filters for recovery of viruses from water.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of a filter with ferric hydroxide floc was reported to adsorb all of the poliovirus in 3.8 liters of water. Brown et al (1,2) found that coating diatomaceous earth with aluminum hydroxide flocs increased its ability to adsorb viruses in § Present address: Department of Biology, Faculty of Natural Science, University of Puerto Rico, Rio Piedras, Puerto Rico.…”
mentioning
confidence: 99%